EFEKTIVITAS MODEL PEMBELAJARAN PJBL BERBASIS STEAM PADA MATA PELAJARAN IPAS DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV - Iswanda Mahmud; Munirah; Razak Umar (Al-mujahidah, 2026)
This study aims to determine the effectiveness of the STEAM-based PJBL learning model in improving the understanding of 4th grade students of SDN 11 Limboto on photosynthesis material. The type of research used is qualitative research. The population of this study is the fourth grade class consisting of 25 students. The learning outcomes obtained after using the STEAM-based PjBL model with Terrarium media on the theme of Photosynthesis The most important process on earth in the fourth grade of SDN 11 Limboto were 21 students who achieved KKTP and 4 students who did not achieve KKTP. Based on the results of the paired sample t-test with the final data obtained from the pretest and posttest results, namely │thitung │ = │11.4025│. Then it can be seen that the value of │thitung│ = │11.4025│> ttable value = 2.06, which means H1 is accepted and H0 is rejected, which means there is an effectiveness of using the STEAM-based PjBL model with terrarium media on student learning outcomes on the theme of Photosynthesis The most important process on earth in Natural and Social Sciences at SDN 11 Limboto, Gorontalo Regency. This effectiveness is also seen from the increase in the average pretest score of 61.68 to 82 in the posttest score.